"N(x, y)=-y-xy, N_x=-y"
"M_y\\not=N_x"
"\\dfrac{M_y-N_x}{N}=\\dfrac{2y-(-y)}{-y-xy}=-\\dfrac{3}{x+1}=P(x)"
Integrating factor
"\\dfrac{x^2+y^2-5}{(x+1)^3}dx+\\dfrac{-y-xy}{(x+1)^3}dy=0"
"M(x, y)=\\dfrac{x^2+y^2-5}{(x+1)^3}, M_y=\\dfrac{2y}{(x+1)^3}"
"N(x, y)=-\\dfrac{y}{(x+1)^2}, N_x=\\dfrac{2y}{(x+1)^3}"
"M_y=\\dfrac{2y}{(x+1)^3}=N_x"
"f(x, y)=\\int(-\\dfrac{y}{(x+1)^2})dy+g(x)"
"=-\\dfrac{y^2}{2(x+1)^2}+g(x)"
"f_x=\\dfrac{y^2}{(x+1)^3}+g'(x)=\\dfrac{x^2+y^2-5}{(x+1)^3}"
"g'(x)=\\dfrac{x^2-5}{(x+1)^3}"
"g(x)=\\int\\dfrac{x^2-5}{(x+1)^3}dx=\\int\\dfrac{x^2+2x+1-2x-2-4}{(x+1)^3}dx"
"=\\int\\dfrac{1}{x+1}dx-2\\int\\dfrac{1}{(x+1)^2}dx-4\\int\\dfrac{1}{(x+1)^3}dx"
"=\\ln(|x+1|)+\\dfrac{2}{x+1}+\\dfrac{2}{(x+1)^2}-C"
"-\\dfrac{y^2}{2(x+1)^2}+\\ln(|x+1|)+\\dfrac{2}{x+1}+\\dfrac{2}{(x+1)^2}=C"
The initial condition "y(0)=1"
"C=\\dfrac{7}{2}"
The solution of the initial value problem
Comments
Leave a comment